Migrants, ethnicity and strategic assimilation - Gil S. Epstein; Ira N. Gang (Rutgers University, Department of Economics, 2006)
Ethnic networks are a way of overcoming informal barriers to trade such as information costs, risk, and uncertainty by building trust and by substituting for the difficulty of enforcing contracts internationally. We study networks which emerge from the interaction (i) between migrants and natives in the host country and (ii) between migrants and natives in their home country. The degree of assimilation and the strength of the networks do not just happen, but are the outcomes of strategic choices of subsets of the migrant population.
Keywords: D74; F23; I20; J61; L140; 330; Assimilation; migration; ethnic networks; contracts